Penerapan Augmented Reality Untuk Pengenalan Ukiran Rumah Gadang Khas Minangkabau Menggunakan Metode 3d Objek Tracking - Rahmiati; Ambyar; M.Giatman; Fransiskus Zoromi; Maharani (SATIN - Sains dan Teknologi Informasi, 2021)
West Sumatra is a famous place which loved for tourist both its natural beauty and culture products such as tourist attraction of the seribu rumah gadang, the pagaruyuang palace and rumah gadang sungai beringin. At the rumah gadang sungai beringin currently there is no tour guide that explains the meaning of the engraving contained in the rumah gadang. Then we need a technology that can be used by visitors through mobile such as Augmented Reality. Augmented Reality is a technology that combines two-dimensional and or three-dimensional virtual objects into a real three-dimensional environment and then projects these virtual objects in a real time. So using Augmented Reality technology can make it easier for users to know and learn the meaning contained in the Minangkabau traditional house carvings. So the first with collecting data carvings in the Rumah gadang sungai beringin as a target model. Furthermore, it is processed by using Unity as the target databases. Features in this application display the details of engraving and pepatah minang equipped with audio. By the presence of mobile-based Augmented Reality technology, it can make it easier for users to understand and learn the carvings that found in the Rumah Gadang sungai beringin